AGRARIAN REFORM, FOOD SOVEREIGNTY AND THE MST: SOCIO-ENVIRONMENTAL IMPACTS OF AGROFUELS PRODUCTION IN THE PONTAL DO PARANAPANEMA REGION OF SÃO PAULO STATE, BRAZIL ( Reforma agrária, soberania alimentar e o MST: impactos socioambientais da produção de...) - Clements, Elizabeth Alice (REVISTA NERA, 2013)
In Brazil, the expansion of sugarcane for ethanol production has fundamentally altered the rural landscape and represents a significant change in the trajectory of the country’s rural development and agrarian reform policies. Current policies are highly skewed in favour of agrofuel industries and are denying landless rural workers and peasant families, like those of Brazil’s Landless Workers Movement (MST), access to land. In addition to the heavy social costs, the agrofuel industry threatens the environment by polluting the air, water and land. This paper elucidates the socio-environmental impacts of the burgeoning sugarcane-ethanol industry in the Pontal do Paranapanema, a region in the extreme west of the São Paulo state with a long history of land-related conflicts. While corporations reap astronomical profits from the agrofuel industry, the costs of agrofuel expansion in the Pontal do Paranapanema and in Brazil have been disproportionally borne by the environment and the most impoverished and marginalized members of society.